2002
DOI: 10.1093/chemse/27.5.445
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Differentiation Gene Mash-1 has a Distinct Pattern of Expression from the Taste Reception-related Genes gustducin and T1R2 in the Taste Buds

Abstract: Taste bud cells have a limited lifespan and are continuously replaced just like other epithelial cells. Although there is some evidence that taste buds may arise from the local epithelium, taste receptor cells have neuronal properties. This implies that there must be a critical stage at which the epithelial precursor cells for taste receptor cells start to exhibit neural properties during the differentiation of the taste receptor cells. The expression of the neural-specific transcription factors Mash-1 and Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…Images were composed in Adobe Photoshop CS5 (Adobe Systems, San Jose, CA, USA) by adjusting the brightness and contrast. although previous in situ hybridization showed that mRNA of Prox1 was expressed intensely in the basal cells but not clearly in the elongate cells in taste buds (Kusakabe et al 2002;Miura et al 2003). The signal for Prox1 was not detected outside the buds, supporting previous in situ hybridization data.…”
Section: Image Processingsupporting
confidence: 81%
See 1 more Smart Citation
“…Images were composed in Adobe Photoshop CS5 (Adobe Systems, San Jose, CA, USA) by adjusting the brightness and contrast. although previous in situ hybridization showed that mRNA of Prox1 was expressed intensely in the basal cells but not clearly in the elongate cells in taste buds (Kusakabe et al 2002;Miura et al 2003). The signal for Prox1 was not detected outside the buds, supporting previous in situ hybridization data.…”
Section: Image Processingsupporting
confidence: 81%
“…Previous in situ hybridization showed that Prox1 is co-expressed with Shh at the beginning when taste bud primordia emerge as Shh-expressing cell clusters both in the FF and SP region at E12.5 and E14.5, respectively (Nakayama et al 2008). In the adult taste buds, Prox1 was co-expressed with Shh in the basal round-shaped cells but, in contrast to the basal cell restricted expression of Shh, Prox1 was also expressed in the elongate cells in taste buds (Kusakabe et al 2002;Miura et al 2003). However, the extent to which elongate cells express Prox1 remains unclear because of a low intensity of in situ hybridization signal in elongate cells.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of progenitor cells contributing to taste buds is not known, and factors controlling division and migration of cells have not been identified. However, neurally derived factors or factors that affect neural precursors may influence this process (Krimm and Hill, 1998;Nag and Wadhwa, 1999;Kusakabe et al, 2002).…”
Section: Normal Developmentmentioning
confidence: 99%
“…[7][8][9] This reaction makes the Gprotein to release alpha unit, which, in bitter receptor it is called as gustducin. 10,11 Gustducin activates enzyme, so that in such condition it results in blocked K + channel, and stimulates PLC (phospholipase C) to activate PIP (phosphoinositol phosphate) to become IP 3 (inositol triphosphate). IP 3 (inositol triphosphate) causes Ca 2+ release from endoplasmic reticulum and mitochondria, resulting in depolarization.…”
Section: Introductionmentioning
confidence: 99%